IMPROVING THE RESULTS OF TREATMENT OF STEROID-DEPENDENT AND STEROIDRESISTANT FORMS OF NON-SPECIFIC ULCERATIVE COLITIS USING PLASMAPHERESIS - Shodmonov A.A.; Kurbaniyazov Z.B; Khuzhabaev S.T; Rustamov I.M (Western European Studies, 2024)
The paper analyses clinical material based on the results of complex examination and treatment of 102 patients with confirmed diagnosis of nonspecific ulcerative colitis. Positive dynamics of general clinical, laboratory parameters and endoscopic picture in patients with steroid-dependent and steroid-resistant forms of nonspecific ulcerative colitis when using for their treatment a course of operations of extracorporeal plasmapheresis testifies to its effectiveness for exacerbation of the disease. Despite the use of minimal doses of corticosteroids during plasmapheresis sessions, in comparison with standard therapy, patients with steroid-dependent and steroid-resistant forms of nonspecific ulcerative colitis achieve remission more often (from 22% to 96%), complications from long-term corticosteroid use are significantly reduced, the possibility of complete cancellation of supportive therapy is achieved, which ultimately leads to an improvement in the quality of life of this category of patients.
Keywords: Non-specific ulcerative colitis; steroid-dependent; steroid-resistant forms